Silver Diamine Fluoride: Transforming Community Dental Caries Program - Gemma Bridge; Anne-Sophie Martel; Marta Lomazzi (Elsevier, 2021)
Introduction: Untreated dental caries is the most frequent childhood chronic disease worldwide. Silver diamine fluoride (SDF) offers a safe and effective alternative treatment, especially for children. Objective: To inform the dental community about the efficacy of SDF in community dental caries programs and to advocate for its use as an affordable and equitable approach to promote health and well-being within the dental setting. Methods: A summary of the literature shared during a webinar about the use and efficacy of SDF in community dental programs hosted by the Oral Health Working Group of the World Federation of Public Health Associations Results: Based on the traditional "drill-and-fill" approach, the current treatment for severe caries is associated with pain, fear, and poor oral health outcomes in later life. Innovative approaches to prevent and control caries are needed. SDF offers an alternative treatment option for caries. It is a practical, affordable, and acceptable option for caries treatment, eliminating the need for general anaesthetic in young children, and improving long-term oral health outcomes. Conclusion: SDF can improve oral health outcomes for community members, especially for individuals from low-socioeconomic settings.